Alterations in thyroid iodine release and the peripheral metabolism of thyroxine during acute falciparum malaria in man - Wartofsky, Leonard (1972)
Previous studies of thyroid function during various infections have yielded conflicting results, but most have suggested an acceleration of peripheral thyroxine (T(4)) turnover during the acute infectious illness. In the present studies, thyroid function was examined by a method allowing simultaneous analysis of both endogenous thyroidal release and peripheral T(4) disposal in normal volunteers after induction of acute falciparum malaria. Subjects received iodide-(125)I, followed in 5-7 days by (131)I-T(4) intravenously. 4 days later, infection was induced by the injection of parasitized red blood cells. Bidaily measurements of serum protein-bound (125)I and protein-bound (131)I, and urinary (125)I and (131)I, together with frequent estimates of serum (127)I-T(4) (Murphy-Pattee) and free T(4) (FT(4)), were made during a control period, during acute illness, and during convalescence. Alterations in the peripheral metabolism of (131)I-T(4) during infection included significant decreases in the fractional disappearance rate for T(4) [(k)], and in the clearance and daily disposal of T(4), all of which returned to control values during convalescence. Total serum (127)I-T(4) increased late in the infected period to become greater during convalescence than either before or during infection, while FT(4) did not increase significantly until convalescence. An analysis of serum (131)I-T(4)/(127)I-T(4) and (131)I-T(4)/PB(125)I ratios confirmed these observations. The slope with time of ratios for urinary (125)I/(131)I, a reflection of thyroidal iodine release, was decreased during infection, but rebounded to control values during the convalescent period. The observed increments in serum (127)I-T(4) concentration in the convalescent phase may reflect in part the slowing of (k), but together with the rising ratios of urine (125)I/(131)I suggests enhanced thyroidal T(4) secretion immediately after the acute illness. Thus, with malarial infection, there appears to be an initial depression followed by a rebound in rates of thyroidal iodine release. In contradistinction to other infections, fractional turnover and daily disposal of hormone is decreased in malaria, perhaps due to hepatic dysfunction and the consequent impairment in cellular deiodinative processes.